Determinants of Postnatal Care and Timing of the First Postnatal Care for Newborns in Ethiopia: Further Analysis of 2019 Ethiopian Demographic and Health Survey - Kebede, Sewnet Adem; Weldesenbet, Adisu Birhanu; Tusa, Biruk Shalmeno (Frontiers in Pediatrics, 2022)
Background: Neonatal mortality remain a persisting public health challenge in Ethiopia. Most of the factors that lead to neonatal deaths could be prevented through postnatal check-ups. However, in Ethiopia, coverage of PNC continues to be low. This study aims to assess the determinant factors of PNC visit and the timing of PNC among newborns in Ethiopia. Methods: Using the Ethiopian Mini Demographic and Health Survey (EMDHS) 2019, a total weighted sample of 2,105 women aged 15-49 giving birth in the 2 years preceding the survey was included in the study. Generalized linear mixed model were separately fitted to identify factors associated with any PNC for newborns delivered at home and health facility. Multinomial logistic regression was used to assess timing of PNC with their associated factors. Results: Overall, only 13% (95% CI; 11.2, 14.0) of the newborns received PNC in Ethiopia. Among newborns delivered at home, attending any PNC were determined by region, maternal educational status and birth order. On the other hand, among newborns delivered in a health facility, region, number of ANC visit and religion were determinants of any PNC. Furthermore, attending first PNC within 48 hours after delivery was determined by region and religion. On the other hand, attending first PNC after 48 hours after delivery was determined by region number of ANC visits, maternal educational status and religion. Conclusion: The finding of current study revealed low coverage of PNC among newborns regardless of place of delivery in Ethiopia. The study makes the following recommendation: increase community health literacy on postnatal care, encourage delivery at health facility, link community home birth with PNC. It will be more valuable if there is sharing of experience from regions which have better PNC coverage.